Report for industrial training at Perbadanan Perpustakaan Awam Negeri Sembilan / Nurhidayahni Kafri - Kafri, Nurhidayahni (Bachelor Degree of Information Science (Hons.) Library Management, 2021)
This paper is a report of activities that have been done by students while undergoing training in organization for the course Industrial Training (IMC690) as this course is compulsory for student to graduate in Bachelor Degree of Information Science (Hons.) Library Management. In this report, it starts from Chapter 1 which is consist the background of the organization and continued with departmental structure and functions. In this report also consist the library facilities and services, the tasks assigned, the programs and activities every student took part and the special project. Besides, knowledge and skill applied during training also written in this report. In Chapter 4, some limitations and recommendations from student were also added at the end of the report with expectation that the organization can take consideration on upgrading for more effective and efficient services in future.